Sexual Education in Riley County Kansas - Brock, Kayla (My University, 2020)
Project 1: Democratic Republic of the Congo As of January 2018 there has been no Hepatitis B prevalence study conducted across the Democratic Republic of the Congo (DRC), however, it is said to be highly endemic in the country (Shindano, Kabinda , & Horsmans , 2018). In June 2019, I traveled with Dr. Carole McArthur to the DRC for the purpose of working with her research team from the Université Protestante au Congo (UPC) Medical School to finalize the protocol for peripheral blood membrane cell (PBMC) freezing. This protocol would be utilized for blood samples collected from individuals who have chronic hepatitis B and are HIV and hepatitis C negative. The goal is to send these blood samples back to the United States in order to conduct laboratory assays on the peripheral blood mononuclear cells and serum as well as determine detailed phenotype of T and B lymphocytes in the Hepatitis B samples. Project 2: Riley County Health Department From July to September of 2019, I served as a clinical intern at the Riley County Health Department (RCHD) studying sexual health education in Manhattan and Riley County. In Riley County, sexually transmitted infections specifically chlamydia, gonorrhea, and syphilis have been on the rise from 2013-2017. Chlamydia rates per 100,000 were around 500 in 2013 compared to 2018 when they rose to just over 800. The Kansas Department of Health and Environment (KDHE) reports the rates of chlamydia from 2013-2017 being higher in Riley County than in the whole state of Kansas (Riley County Ks , n.d.). In 2013 Gonorrhea cases in Riley County were recorded just above 80 per 100,000, and in 2018 this number climbed to 120, these numbers were lower than the Kansas rates where overall the state reached just under 160 in 2017 (Riley County Ks , n.d.). The focus of my project was education in the school systems, because RCHD is seeing higher rates of sexually transmitted infections in the younger population. I examined the current K-12 programs were currently teaching, researched what other states were teaching, and explored national sexual education programs offered. After three months of engaging school nurses, community programs, and program officials, I was able to provide the county commissioners my recommendations on what changes need to be made moving forward with sexual health education in Manhattan and Riley County Kansas.
Keywords: Hepatitis B; Peripheral blood mononuclear cell; sexually transmitted infections; sexual education; sexual health